Studio-based learning via wireless notebooks: a case of a Java programming course. (30th October 2006) - Barak, Miri; Harward, Judson; Lerman, Steven
This paper describes Studio-1.00, a project aimed at enhancing active learning techniques, interactive programming and the exploration of software development, by the use of mobile notebooks and electronic classrooms. We report on a study that investigated undergraduates' in-class use of wireless notebooks and their learning gains. The study was conducted for three semesters, using qualitative and quantitative methodologies for data collection and interpretation. The results indicated that Studio-1.00 had a positive effect on students achievements, especially for the intermediate/low academic level students or those who had little to no earlier knowledge of Java programming. The class observations revealed four main attributes that characterise studio-based learning: (a) hands-on, real-life problem-solving, (b) multi-interactions among learners and instructors, (c) knowledge sharing and (d) receiving immediate feedback. These attributes, which are suggested to enhance students learning gains, could not have been achieved without the inclass use of wireless notebooks.